Analog Models of Fold-and-Thrust Wedges in Progressive Arcs: A Comparison With the Gibraltar Arc External Wedge - Jiménez-Bonilla, Alejandro; Crespo-Blanc, Ana; Balanyá, Juan C.; Expósito, Inmaculada; Díaz-Azpiroz, Manuel (Frontiers in Earth Science, 2020)
The timing and kinematics of the different type of structures and the associated vertical axis-rotations that permit an arcuate external wedge to acquire progressively its curved shape throughout its deformation history --known as progressive arcs-- are key questions in natural cases of arcuate fold-and-thrust belts, that we want to address through analogue modelling. We present laboratory models of fold-and-thrust belts formed with a backstop that deforms in map view to simulate progressive arcs in a thin-skinned tectonic regime. Our set-up makes use of a deformable backstop rigid enough to push-from-behind the initial parallelepiped but deformable in map view. This innovative design permits us to increase the amplitude of the arc indenting in the model as its radius of curvature decreases, that is, it simulates a progressive arc. Taking the Gibraltar arc external wedge situated in the western Mediterranean to scale our models in terms of rheology, velocities and sizes, four types of experiments were made. We varied the type of substratum (sand or silicone), the silicone thickness and the width and length of the initial analogue pack in order to test the influence of each of these parameters on the resulting fold-and-thrust belts. All experiments led to the formation of arcuate wedges where strain was partitioned into: a) arc-perpendicular shortening, accommodated by thrusts which main structural trend is broadly subparallel to the indenter shape and with divergent transport directions, and b) arc-parallel stretching, accommodated by normal and conjugate strike-slip faults. The normal and strike-slip faults contributed to the fold-and-thrust belt segmentation and the formation of independent blocks that rotated clockwise and counterclockwise depending on their position within the progressive arc. Our experiments allow simulating and understanding the finite deformation mode of the external wedge of the Gibraltar arc. Accordingly, they shed light on how an arcuate fold-and-thrust belt can develop progressively in terms of structural trend and transport directions, types and distribution of the structures accommodating strain partition and timing of vertical-axis rotations.